Enterprise Risk Management in The IR4.0 Era: Designing Business Model Options for Bank-of-the-Future - Umar, Nur Fadhilah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
The world is moving at a fast pace with the digital economy. A fourth industrial revolution has emerged, known as Industry Revolution 4.0. Just like autonomous cars promise to be the norm one day, the bank of the future will be mostly digital. However, together with the opportunity, this will also bring with it many new challenges such as cyber-threats. Cyber-threats have been targeting the financial sector worldwide. Downtime can cause widespread disruption and massive damage to an organization's services, bottom line and reputation. Banks are also exposed to market risk, interest rate risk, credit risk, liquidity risk, and operational risk. For any bank, the measurement and management of risk is of the utmost importance. This article will discuss on the business model of the Bank-of-the-Future (BotF), the risk and challenges, as well as the enterprise risk management by using business model canvas (BMC) framework to develop BotF business model options.